Land use as a factor of landslides occurrences in Slovenia - Rup, Davor (Journal for Geography, 2008)
Land use is one of the most important factors for landslide occurrences, because of all connections between natural and socials components of landscape. These are also the reasons for developing different types of land uses, but also have various influences on landslide occurrences. Human activity was always the reason for inducing influences on landslides. It is noted, that where was no human activity or this one was minimal, there were present obstruction influences on landslide occurrences. However, the number of landslides increases every year, and we are convinced that with considerate managing of natural space we can slow down the increasing number of landslides, and consequently decrease the endangering of human lives.